Effects of globalization, energy consumption and ICT on health status in Australia: the role of financial development and education - Mohammad Mafizur Rahman; Khosrul Alam (BMC, 2022)
Abstract Background The outbreak of COVID-19 has alerted governments around the world, including Australia, to think seriously about the health issues. Life expectancy is one of such issues. Therefore, this study tries to reveal the effects of globalization, energy consumption, information and communication technology, financial development, education rate, and economic growth on life expectancy at birth in Australia. Methods Using the data period of 1990-2018, a series of econometric techniques: the Dickey-Fuller generalized least square test, Autoregressive Distributive Lag bounds test, fully modified ordinary least square method and the pairwise Granger causality test, are applied. Results The findings disclose that globalization, renewable energy use, information and communication technology, per capita gross domestic product, education rate, and financial development increased during this period but non-renewable energy use reduced life expectancy at birth. Unidirectional causal associations of the studied variables with life expectancy at birth are also revealed. Conclusions All the outcomes are relevant and useful for articulating an innovative policy in the health sector. The prime policy implication of this work is: the effective, efficient, and inclusive policies considering globalization, renewable and non-renewable energy consumption, information and communication technology, financial development, education rate, and economic growth should be formulated and executed for guaranteeing health status.